Teachers' Perspective of Teaching Language Features in High School: A Qualitative Research - Ramadhani, Pungky (Majapahit Journal of English Studies, 2024)
This study was intended to explore in depth how language features are taught in High School. Qualitative research was used in this study as the research design. The subject of the study was the teacher who has been trained to teach by using the newest curriculum, Independent Curriculum. The data were collected by using two interviews and two observations. The result of this study finds that the teacher understood the language features in a genre-based approach based on the curriculum. The teacher had known that the English lesson was taught by using a genre-based approach. Furthermore, the teacher could teach the language features by following the steps of the genre-based approach. She also structured the tasks communicatively. It is in line with the characteristics of genre-based approach. To sum up, the researcher finds some findings in this study. The teacher follows the steps of a genre-based approach in teaching language features. The process of teaching was delivered inductively. This also means that the teacher applied to focus on meaning. Additionally, the teacher also used indirect instruction. It means the teacher applied student-centered learning. All these indicate that in teaching language features, the teacher follows the rules of the curriculum.